2020
DOI: 10.1101/2020.05.28.106203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell clusters adopt a collective amoeboid mode of migration in confined non-adhesive environments

Abstract: Cell migration is essential to most living organisms. Single cell migration involves two distinct mechanisms, either a focal adhesion- and traction-dependent mesenchymal motility or an adhesion-independent but contractility-driven propulsive amoeboid locomotion. Cohesive migration of a group of cells, also called collective cell migration, has been only described as an adhesion- and traction-dependent mode of locomotion where the driving forces are mostly exerted at the front by leader cells. Here, by studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It is reported that cell motility correlates strongly with the surrounding conditions [7][8][9]. For instance, it is known that a one-dimensional confinement can trigger collective migration [10] and that changes in the density of cells in a two-dimensional substrate can lead to an increase in their motility [11]. Also, it was reported that metastatic cancer cells can navigate a complex porous medium selecting pore shapes to find least-resistance paths to invade [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that cell motility correlates strongly with the surrounding conditions [7][8][9]. For instance, it is known that a one-dimensional confinement can trigger collective migration [10] and that changes in the density of cells in a two-dimensional substrate can lead to an increase in their motility [11]. Also, it was reported that metastatic cancer cells can navigate a complex porous medium selecting pore shapes to find least-resistance paths to invade [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the jittered arrangement of color-coded beeswarms in SuperPlots makes it very difficult to identify differences in the replicates' distributions (Figure 1A). Lacking suitable alternatives, researchers have chosen to show the pooled data distribution using a violin plot that does not contain information about the individual cell distributions within biological replicates (Chavali et al, 2020;Pagès et al, 2020). We thus propose replacing the beeswarm plot with a modified violin plot.…”
mentioning
confidence: 99%
“…For many biological replicates (>18), the shape of the individual stripes of a Violin SuperPlot becomes uninformative. In this limiting case, plotting the replicate means together with their summary statistics on top of a violin plot of the pooled data (Chavali et al, 2020;Pagès et al, 2020) provides a suitable compromise. Violin SuperPlots thus do not replace previous SuperPlot formats (Lord et al, 2020;Goedhart, 2021) but rather complement and extend their scope.…”
mentioning
confidence: 99%
See 2 more Smart Citations